Intracellular delivery and trafficking dynamics of a lymphoma-targeting antibody-polymer conjugate - Berguig, Geoffrey Y. (2012)
Ratiometric fluorescence and cellular fractionation studies were employed to characterize the intracellular trafficking dynamics of antibody-poly(propylacrylic acid) (PPAA) conjugates in CD22+ RAMOS-AW cells. The HD39 monoclonal antibody (mAb) directs CD22-dependent, receptor-mediated uptake in human B-cell lymphoma cells where it is rapidly trafficked to the lysosomal compartment. To characterize the intracellular-releasing dynamics of the polymer-mAb conjugates, HD39-streptavidin (HD39/SA) was dual-labeled with pH-insensitive Alex Fluor 488 and pH-sensitive pHrodo fluorophores. The subcellular pH-distribution of the HD39/SA-polymer conjugates were quantified as a function of time by live-cell fluorescence microscopy, and the average intracellular pH values experienced by the conjugates were also characterized as a function of time by flow cytometry. PPAA was shown to strongly alter the intracellular trafficking kinetics compared to HD39/SA alone or HD39/SA conjugates with a control polymer, poly(methacryclic acid) (PMAA). Subcellular trafficking studies revealed that after 6 hours only 11% of the HD39/SA-PPAA conjugates had been trafficked to acidic lysosomal compartments with values at or below pH 5.6. In contrast the average intracellular pH of HD39/SA alone dropped from pH 6.7 ± 0.2 at 1 hour to pH 5.6 ± 0.5 after 3 hours and pH 4.7 ± 0.6 after 6 hours. Conjugation of the control PMAA to HD39/SA showed an average pH drop similar to HD39/SA. Subcellular fractionation studies with tritium-labeled HD39/SA demonstrated that after 6 hours, 89% of HD39/SA was associated with endosomes (Rab5+) and lysosomes (Lamp2+), while 45% of HD39/SA-PPAA was translocated to the cytosol (lactate dehydrogenase+). These results demonstrate the endosomal-releasing properties of PPAA with antibody-polymer conjugates and detail their intracellular trafficking dynamics and subcellular compartmental distributions over time.